2009
DOI: 10.3354/dao02016
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relationships of haplosporidians deduced from ultrastructural studies

Abstract: We reviewed papers reporting haplosporidian ultrastructure to compare inter-relationships based on ultrastructure with those based on molecular data, to identify features that may be important in haplosporidian taxonomy, and to consider parasite taxonomy in relation to host taxonomy. There were links between the following: (1) the plasmodia of an abalone parasite, Haplosporidium nelsoni and Urosporidium crescens in the release of haplosporosomes; (2) H. costale and H. armoricanum in haplosporosome shape and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…Spore-forming haplosporidians of crustaceans have been described infecting the decapod Rhithro panopeus harrisii tridentatus (Marchand & Sprague 1979) and re cently from freshwater amphipods of the genus Diporeia (Messick 2009). In the recent review by Hine et al (2009), comparison of morphological and molecular features of pathogens reported in the literature as haplosporidians tentatively placed the apparently asporous group in a basal position within the taxon. It should be noted, however, that the asporous characteristic may simply reflect an as-yet undiscovered spore stage in these hosts, or alternatively, their role as an intermediate host to a definitive host in which the spore is formed (Stentiford et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Spore-forming haplosporidians of crustaceans have been described infecting the decapod Rhithro panopeus harrisii tridentatus (Marchand & Sprague 1979) and re cently from freshwater amphipods of the genus Diporeia (Messick 2009). In the recent review by Hine et al (2009), comparison of morphological and molecular features of pathogens reported in the literature as haplosporidians tentatively placed the apparently asporous group in a basal position within the taxon. It should be noted, however, that the asporous characteristic may simply reflect an as-yet undiscovered spore stage in these hosts, or alternatively, their role as an intermediate host to a definitive host in which the spore is formed (Stentiford et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although Perkins (2000Perkins ( , p. 1332 described the Ha plo sporida as 'parasitic protists that form ovoid, walled spores with an orifice covered externally by a hinged lid or internally by a flap of wall material', further assessment of morphological variants plus the addition of molecular phylogenetic analyses have supported inclusion of the apparently non-spore forming genus Bonamia within the Haplosporida (Carnegie et al 2000, Hine et al 2009), a placement that was confirmed with the recent description of the conventionally spore-forming species B. perspora (Carnegie et al 2006). By identifying Bonamia too as a spore-forming genus, even though B. ostreae and B. exitiosa have never been observed to form spores, the discovery of B. perspora underscored the fact that pathological assessment of limited numbers of hosts may only provide a partial view on actual life stages present within a given host species.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations